Nutraceutical interventions for promoting healthy aging in invertebrate models. - Dong, Y.; Guha, S.; Sun, X.; Cao, M.; Wang, X.; Zou, S. (Oxidative medicine and cellular longevity, 2012)
Aging is a complex and inevitable biological process that is associated with numerous chronically debilitating health effects. Development of effective interventions for promoting healthy aging is an active but challenging area of research. Mechanistic studies in various model organisms, noticeably two invertebrates, Caenorhabditis elegans and Drosophila melanogaster, have identified many genes and pathways as well as dietary interventions that modulate lifespan and healthspan. These studies have shed light on some of the mechanisms involved in aging processes and provide valuable guidance for developing efficacious aging interventions. Nutraceuticals made from various plants contain a significant amount of phytochemicals with diverse biological activities. Phytochemicals can modulate many signaling pathways that exert numerous health benefits, such as reducing cancer incidence and inflammation, and promoting healthy aging. In this paper, we outline the current progress in aging intervention studies using nutraceuticals from an evolutionary perspective in invertebrate models.